Thermal decomposition of model compound of algal biomass. Issue 9 (3rd June 2019) - Jabeen, Sidra; Zeng, Zhe; Altarawneh, Mohammednoor; Gao, Xiangpeng; Saeed, Anam; Dlugogorski, Bogdan Z.
Abstract: This contribution investigates thermal decomposition of leucine, as a representative model compound for amino acids in algal biomass. We map out potential energy surface for a wide array of unimolecular and self‐condensation reactions operating in the decomposition of leucine. Decarboxylation and dehydration of leucine ensues by eliminating CO2 and –OH, respectively, from the –COOH group attached to the α ‐carbon. The molecular channel for deamination involves cleavage of NH2 from α ‐carbon of leucine. The activation energies for direct elimination of CO2, NH3, and H2 O from a leucine molecule lie within 20.7 kJ/mol of each other. Activation energies for these decomposition pathways reside below the bond dissociation enthalpy of H–C(α) of 323.1 kJ/mol. The decarboxylation, deamination, and dehydration pathways, via radical‐prompted pathways, systematically require lower energy barriers, in reference to closed‐shell reaction corridors. Detailed computations at the CBS‐QB3 level provide the Arrhenius rate parameters for the unimolecular and bimolecular reactions, and standard enthalpies of formation, standard entropies, and heat capacities for all the products and intermediates. A kinetic analysis of gas‐phase reactions, within the context of a plug‐flow reactor model, accounts qualitatively for the formation of major products observed experimentally in the thermal degradation of the condensed‐phase leucine. Among notable N‐containing species, the model predicts the prevailing of NH3 over HCN and HNCO, in addition to corresponding appreciable concentrations of amines, imines, and nitriles. Our detailed kinetic investigation illustrates a negligible contribution of the self‐condensation reactions of leucine in the gas phase.